Wind tunnel tests of two free-standing lighting protection masts in different arrangements with surroundings roof objects and roof conditions. (1st October 2016) - Flaga, Andrzej; Kłaput, Renata; Augustyn, Marcin
Highlights: Two types of free-standing protection masts with additional supporting ballast were tested in wind tunnel. Wind tunnel experiments were performed at two different terrain roughness categories, different roof conditions, different arrangements with surroundings with surrounding roof objects. Results of experiments were used to elaborate design principles of the free-standing lighting protection masts bases with respect to wind action. Practical approach to lightning protection masts design with respect to their stability problem was worked out. Abstract: The paper presents results of wind tunnel experiments of wind action on two free-standing lighting-protection masts with additional supporting ballast placed on building roofs. Aerodynamic laboratory studies were accomplished in a boundary layer wind tunnel. The main objective of the research was to determine extremal values of aerodynamic coefficients. A cantilevered mast and a tripod mast were tested in different roof conditions and different arrangements with surroundings roof objects. A big influence of aerodynamical interference phenomena between masts and adjacent objects was revealed. Moreover, detailed analysis of the experimental results as well as practical approach to design of such kind of structures with respect to wind action was made.